MULTICULTURAL DA‘WA IN SCHOOLS FROM A SOCIOLOGICAL PERSPECTIVE - Dwiningrum, Siti Irene Astuti (Walisongo: Jurnal Penelitian Sosial Keagamaan, 2014)
Multicultural da‘wa for the sake of building the paradigm of multicultural education is not an easy work due to the determinants in social structure like social, cultural, economic and political determinants. The implementation of multicultural education related to various social elements in society which are not in synergy one another. This article will reveal multicultural preaching carried out in schools and look at the strategies of multicultural education is implemented in schools. Applying qualitative study by describing the initial data associated with a multicultural dakwah activity at the three high schools in Yogyakarta Indonesia, this research concluded that multicultural da‘wa in schools is a combination of several approaches namely the contribution approach, the additive approach, the transformation approach, and the social action approach. Multicultural da‘wa can help students to develop a social identity that to be achieved based on the values of justice, equality and respect the diversity. The strategy developed by the school for implementing multicultural dakwah is by developing language skills, language classes, art performance, the use of cultural symbols, student exchange between tribes or between countries, and uniformity.***Dakwah multikultural untuk membangun paradigma pendidikan multikultural tidak mudah karena struktur masyarakat memiliki diterminan sosial, budaya, ekonomi dan politik. Pelaksanaan pendidikan multikultural terkait dengan berbagai unsur sosial dalam masyarakat yang satu dengan yang lain belum sinergis. Paparan ini akan mengungkap dakwah multikultural yang dilaksanakan di sekolah dan melihat strategi pendidikan multikultural dilaksanakan di sekolah. Melalui penelitian kualitatif dengan menggambarkan data awal terkait dengan aktivitas dakwah multikultural pada tiga SMA di Yogyakarta, Daerah Istimewa Yogyakarta, Indonesia. Penelitian ini berkesimpulan dakwah multikultural di sekolah merupakan kombinasi dari beberapa pendekatan yakni pendekatan kontribusi, pendekatan aditif, pendekatan transformasi, dan pendekatan aksi sosial. Dengan dakwah multikultural dapat membantu siswa untuk mengembangkan identitas sosial yang hendak dicapainya berdasarkan nilai-nilai keadilan, kesetaraan dan menghargai perbedaan. Adapun strategi yang dikembangkan oleh sekolah untuk melaksanakan dakwah multikultural adalah dengan cara mengembangkan kemampuan berbahasa, kelas bahasa, perfomance seni, penggunaan simbol budaya, pertukaran pelajar antar suku atau antar negara, unifomitas.